A construção do programa arquitetônico: uma proposta de ensino para alunos iniciantes - Aragão, Monique Guerreiro Bastos (2017)
Early students of Architecture can benefit from the active learning of the Architectural Program in its first year of college, through a teaching proposal based on a project demand, that allows the approach of the architectural program through the contact with a real client, with mediation of professor. The main objective of this research was the development and application of a teaching proposal, which combines the use of a project demand to engage students in architectural programming, principles of Constructive Alignment to plan teaching, learning and evaluation activities, and the organization and administration of classroom activities with adoption of blended learning. In order to evaluate the teaching proposal, we carried out a case study with 36 beginning students from Nilton Lins University, where we applied the proposal within the discipline of Architecture Project I. Early students performed activities to capture the needs of the client and convert them into what we identified as student´s products. They were a demand register (with the data of the project demand), a list of requirements (compilation of the demands in a list, relating to each area to be designed), and the Architectural Program (reference to the project) at last. Based on the evaluation of these products and other evidences collected during the case study, we found that the teaching proposal had a positive impact on the students' performance, given that under an evaluation using specific assessments and considering their criteria, we ended up with more than 80% of the students delivering architectural programs reaching the concepts "good" and "excellent". Innovative aspects of this work are the teaching and adaptation of the content for beginner students from the needs of a real client, given that the Architectural Program, when approached, has its construction phase suppressed or when considered, it adopts construction models that are distant from the dialogue with the client. In addition, this work provides the implementation of blended learning in Architecture, following an emerging trend in Education. This work has as a product a digital guide with the guidelines for application of the teaching proposal by other teachers.